RITUAL GREBEG BESAR DI DEMAK KAJIAN MAKNA, FUNGSI DAN NILAI - Setiyarini, - (JPP, 2011)
Ritual is a form of activity that is done formally, realized with prayer, dance, music,drama and procedures for purification, pilgrimage, sacrifice, communion as a form ofhuman actualization of the divine order to create a safety and purpose of life is expected.The problems revealed in this study are: the meaning of the ritual process Grebeg Besar,functions, values contained in the Grebeg Besar . Qualitative research with an ethnographicapproach. Data collection techniques performed by the method of observation,interviews and document studies. Analysis of data using ethnographic methods. The resultsof this study found, the meaning of the ritual process, the function of ritual, theGrebeg Besar in Demak namely as a means of ceremonies, entertainment, communication,integration of the value contained in the Grebeg Besar research is expected to be amaterial reflection and pendidikam character for the community and the wider community,especially Demak in general, as found in the meaning of the ritual, the ritual function,meaning and function of music and the values in the Grebeg Besar.Keywords: the meaning of the ritual process, function, value